Airway inflammation in patients with bronchiectasis - Đurđević Nataša (City Medical emergency department, Belgrade, 2021)
Bronchiectasis is a chronic lung disease characterized by an abnormal dilation of the bronchial lumen caused by weakening or destruction of the muscle or elastic components of the bronchial wall, decreased mucous clearance and frequent infections of the respiratory tract. The golden standard for bronchiectasis diagnosis is high-resolution computed tomography (HRCT) of the chest. Inflammation holds a central role in the development of structural lung changes, as well as airway and lung parenchyma damage. Infection and colonization of the respiratory tract contribute to increased inflammation and further damage to the lung. Upon entry into the respiratory tract, the pathogens activate epithelial cells, macrophages and dendritic cells. Activated inflammatory cells secrete chemical mediators which activate the immune response and thus allow the phagocytosis of pathogens. Early diagnosis, appropriate treatment and interruption of the vicious circle between infection and inflammation in patients suffering from bronchiectasis, prevent the development of structural changes to the airways.